Activation of sensory cortex by imagined genital stimulation: an fMRI analysis. (1st January 2016) - Wise, Nan J.; Frangos, Eleni; Komisaruk, Barry R.
Abstract : Background: During the course of a previous study, our laboratory made a serendipitous finding that just thinking about genital stimulation resulted in brain activations that overlapped with, and differed from, those generated by physical genital stimulation. Objective: This study extends our previous findings by further characterizing how the brain differentially processes physical 'touch' stimulation and 'imagined' stimulation. Design: Eleven healthy women (age range 29–74) participated in an fMRI study of the brain response to imagined or actual tactile stimulation of the nipple and clitoris. Two additional conditions – imagined dildo self-stimulation and imagined speculum stimulation – were included to characterize the effects of erotic versus non-erotic imagery. Results: Imagined and tactile self-stimulation of the nipple and clitoris each activated the paracentral lobule (the genital region of the primary sensory cortex) and the secondary somatosensory cortex. Imagined self-stimulation of the clitoris and nipple resulted in greater activation of the frontal pole and orbital frontal cortex compared to tactile self-stimulation of these two bodily regions. Tactile self-stimulation of the clitoris and nipple activated the cerebellum, primary somatosensory cortex (hand region), and premotor cortex more than the imagined stimulation of these body regions. Imagining dildo stimulation generated extensive brain activation in the genital sensory cortex, secondary somatosensory cortex, hippocampus, amygdala, insula, nucleus accumbens, and medial prefrontal cortex, whereas imagining speculum stimulation generated only minimal activation. Conclusion: The present findings provide evidence of the potency of imagined stimulation of the genitals and that the following brain regions may participate in erogenous experience: primary and secondary sensory cortices, sensory-motor integration areas, limbic structures, and components of the 'reward system'. In addition, these results suggest a mechanism by which some individuals may be able to generate orgasm by imagery in the absence of physical stimulation.